Using dialogue to express memories from a meal designer’s gastronomic professional practice - Östergren , Daniel; Eriksson, Lars; Jonsson, Inger (FormAkademisk, 2021)
A meal consists of both tangible and intangible dimensions. Menus and photos may be the only documentation from a meal, but experiences are rarely saved beyond memory. The aim of this study is to design a method for documenting intangible aspects of the professional experience of a meal craftsman, based on the memories associated with the files in an archive. By sorting the archive according to a specific process of documentation we managed to revive and document also the intangible aspects of these meals. In order to access the intangible aspects, a version of the Socratic method of dialogue was developed and used. This is exemplified by a case. The dialogues reunited intangible aspects from the memories of the designer, such as motives and drivers, with the tangible archive documents.